The Development of a Theory of Rational Intertemporal Choice - Germán Loewe (Papers, 2006)
The aim of this article is to describe the evolution of a very dynamic theory: the theory of intertemporal choice. I present the first economic thinking on intertemporal decision-making, and expose how it resulted in Samuelson’s famous discounted utility model; then I describe how and why discounted utility became the standard approach to intertemporal choice in economics through the alleged normative and positive validity of dynamic consistency. Next, I review how the widening of experiments challenged discounted utility together with the dynamic consistency hypothesis, and turned intertemporal choice into a truly interdisciplinary field of research. Finally, I discuss the foundations of dynamic consistency and prove that it is neither normatively nor descriptively justified as a necessary axiom of rational intertemporal choice. I also show how until only recently, the dynamic consistency debate has had a blinding effect on the relative importance attributed to other fundamental anomalies in discounted utility. And this blinding effect can be regarded as a further side-effect of the excessive role given to dynamic consistency along these years. I thus conclude that dynamic consistency has been acting as an invisible straitjacket obstructing the development of intertemporal choice theory, and that it is only by undoing it that this field of research can achieve in the future a satisfactory understanding of human decision-making.